Engaging the tropical majority to make ocean governance and science more equitable and effective - Spalding, Ana; Grorud-Colvert, Kirsten; Allison, Edward (Eddie); Amon, Diva; Collin, Rachel; de Vos, Asha; Friedlander, Alan; Johnson, Steven; Mayorga, Juan; Paris, Claire; Scott, Cinda; Suman, Daniel; et al. (Nature Portfolio, 2023)
How can ocean governance and science be made more equitable and effective? The majority of the world’s ocean-dependent people live in low to middle-income countries in the tropics (i.e., the ‘tropical majority’). Yet the ocean governance agenda is set largely on the basis of scientific knowledge, funding, and institutions from high-income nations in temperate zones. These externally driven approaches undermine the equity and effectiveness of current solutions and hinder leadership by the tropical majority, who are well positioned to activate evidence-based and context-specific solutions to ocean-sustainability challenges. Here, we draw together diverse perspectives from the tropics to propose four actions for transformational change that are grounded in perspectives, experiences, and knowledge from the tropics: 1. Center equity in ocean governance, 2. Reconnect people and the ocean, 3. Redefine ocean literacy, and 4. Decolonize ocean research. These actions are critical to ensuring a leading role for the tropical majority in maintaining thriving ocean societies and ecosystems.